Herramienta diagnóstico para competencia técnica de laboratorios de ensayo y calibración (2022)
Private or public organizations that have a testing, calibration or research laboratory as part of their processes and that provide services to users are aware of the importance and the need to accredit these methodologies and demonstrate their technical competencies as a strategy to obtain recognition and positioning in the sector, providing their results with solidity and confidence in the face of market competition. Therefore, the diagnosis of compliance with the general requirements for technical competence of testing and calibration laboratories with respect to ISO/IEC 17025:2017 takes on great importance. As a result of the research process, a tool developed in collaboration with the Planning Group and the Laboratories Directorate of the Colombian Geological Survey is presented, which was applied to six laboratory tests to assess the requirements compliance degree with the requirements for the future purpose of accrediting technical competence before competent bodies. The results show the levels of compliance with the requirements of the aforementioned standard, the application of the tool allowed its content validation taking as a sample the entity, the results were positive regarding its construction and consistency in compliance with the  NTC-ISO/IEC 17025:2017 standard requirements.